THE ETHNOLINGUISTIC VITALITY OF GULGULIA - Mishra, Sneha; Rahman, Md Mojibur (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
Language death is a phenomenon with symptoms related to demeaning vocabulary count and depletion of domains of language use along with the simplicity of linguistic structures. It commences by exhibiting traits of a declining number of fluent speakers, dwindling attitude of the speakers with regard to their heritage language, language shift, lack of inter-generational language transfer accompanied by a feeling that heritage language is inferior to outside languages, and Gulgulia exhibits every trait of such a dying language. It has become a waning language that is very close to its permanent extinction. The present study elucidates the ethnolinguistic vitality of Gulgulia tested through chosen sociolinguistic parameters which were found suitable to Gulgulia’s scenario. It also explores the linguistic situation of the Gulgulian community in Dhanbad, the community members’ language use in their homes and in their miscellaneous interethnic interactions and examines what relation prevails between the community’s language preference and their vitality. It was found that speaker variables, such as age, gender, and language competence governed the speaker’s attitude toward the heritage language. The location of the speech community is also a regulating factor in determining the inclination for preservation or attrition of the native language. The analysis of the speech behavior in the Gulgulian community confirms the loss of major genres such as the art of narration. Out of all the genres of language use, only two are surviving, which is alarming.